PENGARUH EKSTRAK DAUN BELUNTAS (Pluchea indica (L.) Less) 25% TERHADAP BIOFILM STREPTOCOCCUS MUTANS - in vitro - Clarissa Bonita Syaravina; Rizki Amalina; Eko Hadianto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2018)
Background: Bioflm begins with formation of pelicle and within a minutes the colonization of bacteria attached to surface of the teeth. One of early bacteria attached was Streptococcus mutans. This study used 25% beluntas leaf extract in inﬂuencing the growth of Streptococcus mutans bioflm. The purpose of study was to investigated eﬀect of 25% beluntas leaf extract on Streptococcus mutans bioflm.Methods: This research was experimental laboratory with post test only control design, consist of four treatment groups, 25% beluntas leaf extract and 0.12% chlorhexidine incubated 24 hours and 48 hours. Bioflm formation was measured by calculating Optical Density using a spectrophotometer. Data analysis was performed using One Way Anova test followed by Post Hoc LSD test.Result: The results showed that beluntas leaf extract could inﬂuence theformation of S.mutans bioflm but the eﬀect in inhibiting bioflm formation is still not as good as chlorhexidine. It is known from the results of One Way Anova 25% beluntas leaf extract and 0.12% chlorhexidine incubated for 24 hours and 48 hours showed signifcant diﬀerence (p <0.05).Conclusion: The conclusion of this research is the eﬀect of beluntas leaf extract (Pluchea indica (L.) Less) 25% to Streptococcus mutans bioflm in vitro.